Theory of mind as a link between oxytocin and maternal behavior. (June 2018) - MacKinnon, Anna L.; Carter, C. Sue; Feeley, Nancy; Gold, Ian; Hayton, Barbara; Santhakumaran, Sangeetha; Zelkowitz, Phyllis
Highlights: Pregnancy oxytocin predicted better Reading the Mind in the Eyes Test (RMET) scores. RMET performance predicted more structuring and less intrusive maternal behavior. Mothers' tendency to use mind-related comments predicted greater sensitivity. There was an indirect effect of oxytocin on maternal behavior via RMET performance. Oxytocin changes in late pregnancy may enhance theory of mind and thereby caregiving. Abstract: Background: Oxytocin is a neuropeptide associated with maternal behavior. However the mechanisms underlying this link remain unclear. In a previous study we observed an indirect effect of increased plasma oxytocin during late pregnancy on early postpartum maternal interactive behavior via theory of mind, as assessed by the Reading the Mind in the Eyes Test (RMET). The current study aimed to extend these findings by testing whether this indirect effect would hold longitudinally for maternal behavior at 2–3 years postpartum, as well as for an additional observational measure of maternal mind-mindedness. Method: The original sample of 316 pregnant women ( M age  = 31.92 years) was assessed at 12–14 weeks gestation (T1), 32–34 weeks gestation (T2), and 7–9 weeks postpartum (T3). Follow-up measures were taken at 2–3 years postpartum (T4). Results: Mothers' RMET performance (T3) was associated with more structuring and less intrusive maternal behavior at 2–3 years (T4), while their tendency to use mind-related comments (T3) was associated with greater sensitivity (T4). Bootstrap estimates also revealed a significant indirect effect of plasma oxytocin levels during late pregnancy (T2) on maternal structuring and non-intrusive behavior at 2–3 years postpartum (T4) through RMET performance (T3). Conclusions: Results: of the current study confirm and extend the previous findings, demonstrating that theory of mind may represent a social cognitive mechanism linking endogenous oxytocin and maternal behavior. Important changes in the oxytocinergic system during late pregnancy may help prepare for motherhood by promoting the awareness of social cues, which in turn promote maternal behavior from the early postpartum to the early childhood years.